A história local de São João de Pirabas-Pa no ensino de História: debates e representações - COSTA, Thamires Souza da (2024)
This research seeks to analyze, problematize and promote discussions regarding the inclusion of local history teaching in history classes at the Guajarina Menezes Silva school, located in the Municipality of São João de Pirabas-Pa. With this, reflect the importance of representing local elements in the teaching and learning of students in the final years of elementary school. The aim is to contribute to the process of building the student's school historical knowledge, through methodological proposals that raise awareness of the different uses of local history teaching in the history discipline and, in this sense, make people think and reflect on the role of teaching practice in the teaching process. /learning. To support the research, we sought to dialogue with authors who discuss and emphasize the relevance of teaching local history in the educational life of students, therefore bibliographical research was carried out, analyzes of official education documents, school normative documents, in addition to resort to oral sources, necessary for the proper development of investigations. Through the analyzes it was possible to understand the factors that affect the effectiveness of teaching local history in practice in the classroom. As a result, it was possible to think about and apply the “Cultural Fair” pedagogical project in the school space with 9th grade students, as a strategy to enable and value local elements through teaching local history.